Message queue telemetry transport and lightweight machine-to-machine comparison based on performance efficiency under various scenarios - Drishti Singh; Ria Singh; Aryan Gupta; Ambika Vishal Pawar (International Journal of Electrical and Computer Engineering (IJECE), 2022)
Internet of things (IoT) is been advancing over a long period of time in many aspects. For data transfer between IoT devices in a wireless sensor network, various IoT protocols are proposed. Among them, the most widely used are constrained application protocol (CoAP) and message queue telemetry transport (MQTT). Overcoming the limitations of CoAP, lightweight machine-to-machine (LwM2M) framework was designed above CoAP. Recent statistics show that LwM2M and MQTT are the widely used, but LwM2M is still less used than MQTT. Our paper is aimed at comparing both MQTT and LwM2M on the basis of performance efficiency, which will be achieved by sending same file through both protocols to the server. Performance efficiency will be calculated in two scenarios, i) when the client makes a connection with the server i.e., while initial connection and ii) while sending data file to server i.e., while data transfer. Both the protocols will be tested on the number of packets sent and the variability of packet size throughout the session. Experimental results indicated that LwM2M outperformed MQTT in both above scenarios by almost 69%. Therefore, we concluded by stating that LwM2M is best choice over MQTT, but MQTT can still be used in some situations if necessary.